Variation of the geomagnetic field in Costa Rica during the total solar eclipse of July 11, 1991 - Brenes, Jorge (1993)
Ground measurements of the geomagnetic field, during the total solar eclipse of July 11, 1991. were carried out at three sites in Costa Rica located within the eclipse´s path of totality. Near totality, there was a significant change in the total intensity, F. Its normal decrease in the afternoon hours was interrupted during a period of about 45 min, in which F varied very little. This was due mainly to a small variation in horizontal intensity, H during such a period. The departure of F from normal lasted abput 100 min; its maximun departure was near 10 nT and ocurred about 38 min after totality. The declination, D, also experienced a small change (about 2.3 min) during the total period of eclipse. The vertical intensity, Z, and the inclination I, did not show significant changes.